2004
DOI: 10.1260/0263617041503499
|View full text |Cite
|
Sign up to set email alerts
|

Peanut Shell Activated Carbon: Adsorption Capacities for Copper(II), Zinc(II), Nickel(II) and Chromium(VI) Ions from Aqueous Solutions

Abstract: ABSTRACT:The adsorption of copper(II), zinc(II), nickel(II) and chromium(VI) ions from aqueous solutions onto an activated carbon produced from peanut shell was studied as a function of the concentration of the ions and the pH value. The amounts of Cu(II), Zn(II) and Ni(II) ions adsorbed increased with increasing equilibrium pH of the solution, while the uptake of Cr(VI) ions decreased. For Cr(VI) ions, maximum uptakes were found at a pH below the point of zero charge of the adsorbent (pH pzc ). The amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Some low cost activated carbons used for removing of Hexavalent Chromium ions such as groundnut husk [19], agrowaste [20], neem leaves [21], sawdust [22], wheat bran [23], rice bran [24], sago waste [25], green coconut shell [26], hazelnut shell [27], olive stone [28], gingelly oil cake [29], and peanut shell [30,31] have all been reported as useful for preparing adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Some low cost activated carbons used for removing of Hexavalent Chromium ions such as groundnut husk [19], agrowaste [20], neem leaves [21], sawdust [22], wheat bran [23], rice bran [24], sago waste [25], green coconut shell [26], hazelnut shell [27], olive stone [28], gingelly oil cake [29], and peanut shell [30,31] have all been reported as useful for preparing adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural biowaste materials have been tested for the removal of heavy metal ions from water, including sawdust (Garg et al 2004), bamboo (Dula et al 2014), neem leaves (Babu and Gupta 2008), olive cake (Dakiky et al 2002), green coconut shell (Pino et al 2006), groundnut husk (Dubey and Gopal 2007), and peanut shell (Romero et al 2004). Biowaste is a suitable candidate for the preparation of AC because of its underutilization and/or availability in large quantities (Garg et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a variety of agricultural waste can remove toxic heavy metal ions effectively, such as rice bran [4], rice husk [5], bark [6], peanut shells [7], coconut shell [8], wheat straw [9], waste tea leaves [10], bagasse [11], water hyacinth [12], coffee beans [13], a variety of plants, sawdust [14], etc. [15,16].…”
Section: Introductionmentioning
confidence: 99%